Enhancing students critical thinking skills in writing by promoting ESP-based language learning environment - Subramaniam, Shivaraj; Sulaiman, Salsuhaida; Nadarajan, Kirubashini; Yaacob, Zuriani; Magiman, Mohamad Maulana; Abbas, Mohd Saleh (ASR Research India, 2022)
"Flipped classroom" business English classes are required at most universities that teach economics, and this study will investigate how these classes help students learn critical thinking skills and improve their academic performance, as well as what students think of this model. A multimedia textbook titled "English for Business" enhances the learning environment. This was an exploratory investigation that used a range of methodologies. The study examined children's critical thinking and academic progress (learning outcomes). Surveys of students' critical thinking abilities and placement assessments were utilized to acquire statistical data. The Cronbach alpha coefficients were used to evaluate the critical thinking test outcomes, and the aggregated data was analyzed using SPSS AMOS statistical software. The study revealed that teaching ESP and Business English to Economics students via the "flipped schoolroom" technique can enrich both the learners' and instructors' education experiences. Because students are held responsible for their progress, this method develops critical thinking skills and academic accomplishment by using a variety of teaching methods. A student-centered approach replaces the teacher-centered approach in the preceding paradigm. Students at colleges and universities are increasingly using language as a medium of instruction rather than rote memorization, as demonstrated by business English and English as a Second Language (ESL) programs.